NAVIGATING THE DIGITAL REVOLUTION: CHALLENGES AND OPPORTUNITIES FOR JOURNALISM IN NEPAL - 1 Laxmi Prasad Devkota Upadhyay, 2 Dr. Prachi Chaturvedi (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The internet's revolution in journalism, expanding information sharing and eroding traditional media's exclusivity, is exemplified by social media's surpassing influence and reach, yet journalists face with maintaining standards amidst this evolving landscape, striving to harness social media's power for effective communication. The interactive features of social media have transformed journalism into a forum whose primary function is the exchange of ideas. Blogs, YouTube, Twitter, and Facebook, among other platforms, have become increasingly important in the dissemination of news. This research investigates effects of new media trends among journalists of Nepal. . A qualitative cross-sectional study was conducted, involving purposeful selection of five key informants from Kathmandu's media based on their expertise and knowledge for Key Informant Interviews, followed by thematic analysis. This study found that modern journalism in Nepal has undergone a digital revolution, driven by technological advancements and the widespread adoption of new media tools like social media networks and smartphone. While journalists increasingly rely on platforms like social media for news dissemination, challenges such as verifying information accuracy and maintaining ethical standards persist. However, issues like resource scarcity, technological constraints, and ethical dilemmas persist, necessitating the development of clear guidelines and continuous media literacy enhancement to ensure responsible and effective journalism in Nepal's dynamic media environment.